Role of Oncogenes and Tumor-suppressor Genes in Carcinogenesis: A Review - KONTOMANOLIS, EMMANUEL N.; KOUTRAS, ANTONIOS; SYLLAIOS, ATHANASIOS; SCHIZAS, DIMITRIOS; MASTORAKI, AIKATERINI; GARMPIS, NIKOLAOS; DIAKOSAVVAS, MICHAIL; ANGELOU, KYVELI; TSATSARIS, GEORGIOS; PAGKALOS, ATHANASIOS; NTOUNIS, THOMAS; FASOULAKIS, ZACHARIAS (Anticancer research, 2020)
Cancer is a medical condition which has a molecular basis. Proto-oncogenes are the first regulatory factors of this biological process. They act in transmitting signals, resulting as growth factors. Modifications of these genes, called oncogenes, lead to the appearance of cancer cells. The activation process leading to proto-oncogenes are chromosomal translocation, point mutation, and gene amplification. Concerning the clonal theory of oncogenesis, it is believed that a tumor starts from a cell. Furthermore, there is close association between tumor development and inhibition of apoptosis or programmed cell death, providing cell immortality. Angiogenesis and angiogenic factors found to be expressed in tumors and may play a key role in tumor formation and development. Tumor-suppressor genes block the growth of cancer and contribute to the normal development of cells. This article highlights the evidence that neoplasms develop as the after-effect of the increase of acquired and physical genetic variations in proto-oncogenes and tumor-suppressor genes; these form a target group in the cells of neoplasms. Tumor formation and development are characterized by individual processes, working synergistically, and an understanding of each individual process may provide a better basis for further anticancer research.